Invisible Consequences: The Health Hazards of "Women’s Work" in New Zealand - Duncan, Dawn (Victoria University of Wellington Law Review, 2019)
Gordon Anderson has written extensively on the changes in New Zealand’s labour laws that have occurred since the late 1960s, and the consequences of these changes for workers. This period saw the narrowing and individualising of work health and safety, the separation of health and safety from other areas of employment relations and the workers’ compensation functions of the Accident Compensation Corporation (ACC) scheme. This article explores one of the largely invisible consequences of these shifts, arguing that gaps have emerged between these areas of law, and these gaps fall disproportionately over the types of work that women typically perform. This article outlines the current gaps in the law and identifies the areas in need of reform.